Defining low anterior resection syndrome: a systematic review of the literature. (2nd August 2017) - Keane, C.; Wells, C.; O'Grady, G.; Bissett, I. P.
Abstract: Aim: There is increasing awareness of the poor functional outcome suffered by many patients after sphincter‐preserving rectal resection, termed 'low anterior resection syndrome' (LARS). There is no consensus definition of LARS and varying instruments have been employed to measure functional outcome, complicating research into prevalence, contributing factors and potential therapies. We therefore aimed to describe the instruments and outcome measures used in studies of bowel dysfunction after low anterior resection and identify major themes used in the assessment of LARS. Method: A systematic review of the literature was performed for studies published between 1986 and 2016. The instruments and outcome measures used to report bowel function after low anterior resection were extracted and their frequency of use calculated. Results: The search revealed 128 eligible studies. These employed 18 instruments, over 30 symptoms, and follow‐up time periods from 4 weeks to 14.6 years. The most frequent follow‐up period was 12 months (48%). The most frequently reported outcomes were incontinence (97%), stool frequency (80%), urgency (67%), evacuatory dysfunction (47%), gas–stool discrimination (34%) and a measure of quality of life (80%). Faecal incontinence scoring systems were used frequently. The LARS score and the Bowel Function Instrument (BFI) were used in only nine studies. Conclusion: LARS is common, but there is substantial variation in the reporting of functional outcomes after low anterior resection. Most studies have focused on incontinence, omitting other symptoms that correlate with patients' quality of life. To improve and standardize research into LARS, a consensus definition should be developed, and these findings should inform this goal.